Elements of banking intermediation in the Algerian Banking system and the means to activate it - Habbar Abderezak, Dr. (Arab Economic and Business Journal, 2014)
Algerian banks are so far the main source of funding for the Algerian economy including the public sector. In this context, we found that the banking sector is still subject to the trends of government authorities to justify this relationship by looking forward to achieving economic development, but on the other side this restricts the activity of banks in terms of banking intermediation. Banking intermediation raises several interrelated issues for banks, the central bank and the Treasury. It is linked to the gross domestic product, money supply and bank liquidity, etc. These elements will be examined in this article to learn the elements of bank intermediation in the Algerian banking system and ways of strengthening it.